Virology Journal - Wang, Linfa; Poon, Leo.; McLachlan, Alan.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Virology Journal is an open access, peer reviewed journal that considers articles on all aspects of virology, including research on the viruses of animals, plants and microbes. The journal welcomes basic research as well as pre-clinical and clinical studies of novel diagnostic tools, vaccines and anti-viral therapies. The Editorial policy of Virology Journal is to publish all research which is assessed by peer reviewers to be a coherent and sound addition to the scientific literature, and puts less emphasis on interest levels or perceived impact. Virology Journal will feature articles on human, animal, plant, insect, bacterial, and fungal viruses. The journal will also publish articles on molecular aspects of the control and prevention of viral infections with vaccines and antiviral agents and on the use of viruses as gene therapy vectors, as well as research on other agents such as prions. The approaches and techniques used are expected to encompass many disciplines, including molecular genetics, molecular biology, biochemistry, biophysics, structural biology, cell biology, immunology, morphology, genetics and pathogenesis.
Keywords: Virology; Virology